Pink Dollars: Gay and lesbian Film Festivals and the Economy of Visibility - Rhyne, Ragan (2007)
This dissertation is about gay and lesbian film festivals, the first of which was founded in San Francisco in 1977 and subsequently served as a model for their international proliferation over the next thirty years. While the films programmed in these festivals have received a great deal of attention from scholars and critics, the festival institution itself has received less consideration. This dissertation narrates the history of gay and lesbian film festivals through an economic lens, asking how fundraising practices have been deployed in the community building projects of festivals, how the administrative structures of festivals as nonprofit organizations have been leveraged by the state toward the management of new social movements, and how these nonprofits have participated in the identification and cultivation of populations as niche markets by the commercial sector. This historical schema will offer an alternative model for understanding queer image production, not through a textual analysis of those images, but through an examination of the material circumstances of their circulation and distribution. This dissertation is not simply about the ways that community organizations like film festivals have been strategically engaged by the state and the market in the management and exploitation of gays and lesbians, it argues that gays and lesbians themselves have articulated their politics, artistic practice, and discourse of community within (and against) the parameters defined by the demands of organizational sustainability. Furthermore, this dissertation will illustrate why taking economic activity seriously as a part of the material practices of queer image production answers crucial questions about the ways that sexuality operates as a category of governance. The history of gay and lesbian film festivals, and their regulation through the administrative structures of the nonprofit sector, is part of a much larger history of political struggle and the development of new social movements over the past three decades.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Struggles for Representation: African American Documentary Film and Video - Reid, Mark A. (American Literature, 2000)
Struggles for Representation examines over 300 non-fiction films by more than 150 African American film/videomakers and includes an extensive filmography, bibliography, and excerpts from interviews with film/videomakers. In eleven original essays, contributors explore the extraordinary scope of these aesthetic and social documents and chart a previously undiscovered territory: documentaries that examine the aesthetic, economic, historical, political, and social forces that shape the lives of black Americans, as seen from their perspectives.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Witch’s Flight: The Cinematic, the Black Femme, and the Image of Common Sense - Keeling, Kara (Duke University Press, 2007)
Kara Keeling contends that cinema and cinematic processes had a profound significance for twentieth-century anticapitalist Black Liberation movements based in the United States. Drawing on Gilles Deleuze’s notion of “the cinematic”—not just as a phenomenon confined to moving-image media such as film and television but as a set of processes involved in the production and reproduction of social reality itself —Keeling describes how the cinematic structures racism, homophobia, and misogyny, and, in the process, denies viewers access to certain images and ways of knowing. She theorizes the black femme as a figure who, even when not explicitly represented within hegemonic cinematic formulations of raced and gendered subjectivities, nonetheless haunts those representations, threatening to disrupt them by making alternative social arrangements visible.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Queer Cinema in the World - Padva, Gilad (Historical Journal of Film, Radio and Television, 2019)
Karl Schoonover and Rosalind Galt’s Queer Cinema in the World initially proposes a radical comparative vision of cinema’s queer globalism. It aims to explore how queer filmmaking intersects with international sexual cultures, geopolitics, and aesthetics to disrupt dominant modes of world making.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Hollywood at the Intersection of Race and Identity - Konzett, Delia Caparoso. (Rutgers University Press, 2020)
Hollywood at the Intersection of Race and Identity explores the ways Hollywood represents race, gender, class, and nationality at the intersection of aesthetics and ideology and its productive tensions. This collection of essays asks to what degree can a close critical analysis of films, that is, reading them against their own ideological grain, reveal contradictions and tensions in Hollywood’s task of erecting normative cultural standards? How do some films perhaps knowingly undermine their inherent ideology by opening a field of conflicting and competing intersecting identities? The challenge set out in this volume is to revisit well-known films in search for a narrative not exclusively constituted by the Hollywood formula and to answer the questions: What lies beyond the frame? What elements contradict a film’s sustained illusion of a normative world? Where do films betray their own ideology and most importantly what intersectional spaces of identity do they reveal or conceal?
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

De-Westernizing Film Studies - Ba, Saer Maty; Higbee, Will (Routledge, 2012)
De-Westernizing Film Studies aims to consider what form a challenge to the enduring vision of film as a medium - and film studies as a discipline - modelled on ‘Western’ ideologies, theoretical and historical frameworks, critical perspectives as well as institutional and artistic practices, might take today. The book combines a range of scholarly writing with critical reflection from filmmakers, artists & industry professionals, comprising experience and knowledge from a wide range of geographical areas, film cultures and (trans-)national perspectives. In their own ways, the contributors to this volume problematize a binary mode of thinking that continues to promote an idea of ‘the West and the rest’ in relation to questions of production, distribution, reception and representation within an artistic medium (cinema) that, as part of contemporary moving image culture, is more globalized and diversified than at any time in its history. In so doing, De-Westernizing Film Studies complicates and/or re-thinks how local, national and regional film cultures ‘connect’ globally, seeking polycentric, multi-directional, non-essentialized alternatives to Eurocentric theoretical and historical perspectives found in film as both an artistic medium and an academic field of study. The book combines a series of chapters considering a range of responses to the idea of 'de-westernizing' film studies with a series of in-depth interviews with filmmakers, scholars and critics. Contributors: Nathan Abrams, John Akomfrah, Saër Maty Bâ, Mohammed Bakrim, Olivier Barlet, Yifen Beus, Farida Benlyazid, Kuljit Bhamra, William Brown, Campbell, Jonnie Clementi-Smith, Shahab Esfandiary, Coco Fusco, Patti Gaal-Holmes, Edward George, Will Higbee, Katharina Lindner, Daniel Lindvall, Teddy E. Mattera, Sheila Petty, Anna Piva, Deborah Shaw, Rod Stoneman, Kate E. Taylor-Jones
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Contemporary Jewish Reality in Germany and Its Reflection in Film - Dorchain, Claudia Simone; Wonnenberg, Felice Naomi (De Gruyter, 2012)
The notion of “self” and “other” and its representation in artwork and literature is an important theme in current cultural sciences as well as in our everyday life in contemporary Western societies. Moreover, the concept of “self” and “other” and its imaginary dichotomy is gaining more and more political impact in a world of resurfacing ideology-ridden conflicts. The essays deal with Jewish reality in contemporary Germany and its reflection in movies from the special point of view of cultural sciences, political sciences, and religious studies. This anthology presents challengingly new insights into topics rarely covered, such as youth culture or humor, and finally discusses the images of Jewish life as realities still to be constructed.
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; _Nettoyé